То the relativistic kinetic and hydrodynamic theory - B. V. Alexeev; I. V. Ovchinnikova (Тонкие химические технологии)
On the basis of statistical description the movement of relativistic particles without external forces is considered. The hydrodynamic form of the Dirac equation is suggested. The Lorentz invariant form of the non-local Alexeev equation (generalized Boltzmann equation) was obtained. These results lead to the possibility of construction of relativistic quantum hydrodynamics. This paper can also be considered as continuation of the known monograph (Boris V. Alexeev, Generalized Boltzmann Physical Kinetics. Elsevier. 2004).